Effect of obesity status on adolescent bone mineral density and saturation effect: A cross-sectional study - Wang, Gao-Xiang; Fang, Ze-Bin; Li, Hui-Lin; Liu, De-Liang; Chu, Shu-Fang; Zhao, Heng-Xia (Frontiers in Endocrinology, 2022)
Background: The effect of obesity status on bone mineral density (BMD) in adolescents and whether there is a saturation effect is still insufficient. A cross-sectional study of adolescents aged 12–19 was conducted to investigate them. Methods: Weighted multivariate linear regression models were used to assess the relationship between obesity status and BMD via datasets from the National Health and Nutrition Examination Survey 2011–2018. The nonlinear relationships and saturation values were ascertained by fitting smooth curves and analyzing saturation effects. At the same time, the subgroup stratified analysis was also performed. Results: 4056 adolescents were included in this study. We found that body mass index (BMI) and waist circumference (WC) were significantly associated with total BMD, which remained significant in subgroups stratified by age, gender, standing height, and ethnicity. We also noticed an inverse correlation between left leg fat/lean mass and left leg BMD, which was only significant in males and other races. Fitting smooth curve and saturation effect analysis showed that BMI, WC, left leg fat/lean mass, and BMD had a specific saturation effect. There was a saturation effect on bone mineral density in adolescents with a BMI of 22 kg/m2, a WC of 70.5 cm, or a left leg fat/lean mass of 0.2994. Conclusions: We found a positive saturation effect of BMI and WC with BMD and a negative saturation effect of left leg fat/lean mass with BMD. Appropriate obesity status allows adolescents to have better bone mass development but not excessive obesity